Amniotic fluid embolism: antepartum, intrapartum and demographic factors. (May 2015) - Fong, Alex; Chau, Cindy T.; Pan, Deyu; Ogunyemi, Dotun A.
Abstract Objective: To describe the incidence, antepartum, intrapartum and postpartum risk factors, and mortality rate of amniotic fluid embolism (AFE). Methods: We used 2001–2007 California health discharge data to identify cases of AFE by ICD-9 codes. Results: Of 3 556 567 deliveries during the time period, we identified 182 cases of AFE, resulting in a population incidence of 5.1 in 100 000. Twenty-four of the cases resulted in death, giving a case fatality rate of 13.2%. Non-Hispanic blacks had a higher than 2-fold odds of developing AFE. AFE increased significantly with maternal age, most significantly after age 39. Cardiac disease had a nearly 70-fold higher association with AFE, cerebrovascular disorders had a 25-fold higher association, while conditions such as eclampsia, renal disease, placenta previa and polyhydramnios had nearly 7- to 13-fold higher associations. Classical cesarean delivery, abruption placentae, dilation and curettage, and amnioinfusion were all procedures highly associated with AFE. Conclusion: Several antepartum and peripartum conditions and procedures are associated with significantly higher risks of amniotic fluid embolism. This information may contribute to a better understanding of the pathophysiology of AFE and potentially help identify those at the highest risk of developing this morbid condition.